Potential Contribution of Work-Related Psychosocial Stress to the Development of Cardiovascular Disease and Type II Diabetes: A Brief Review - Kristine M. Krajnak (SAGE Publishing, 2014)
Two of the major causes of death worldwide are cardiovascular disease and Type II diabetes. Although death due to these diseases is assessed separately, the physiological process that is attributed to the development of cardiovascular disease can be linked to the development of Type II diabetes and the impact that this disease has on the cardiovascular system. Physiological, genetic, and personal factors contribute to the development of both these disorders. It has also been hypothesized that work-related stress may contribute to the development of Type II diabetes and cardiovascular disease. This review summarizes some of the studies examining the role of work-related stress on the development of these chronic disorders. Because women may be more susceptible to the physiological effects of work-related stress, the papers cited in this review focus on studies that examined the difference in responses of men or women to work-related stress or on studies that focused on the effects of stress on women alone. Based on the papers summarized, it is concluded that (1) work-related stress may directly contribute to the development of cardiovascular disease by inducing increases in blood pressure and changes in heart rate that have negative consequences on functioning of the cardiovascular system; (2) workers reporting increased levels of stress may display an increased risk of Type II diabetes because they adopt poor health habits (ie, increased level of smoking, inactivity etc), which in turn contribute to the development of cardiovascular problems; and (3) women in high demand and low-control occupations report an increased level of stress at work, and thus may be at a greater risk of negative health consequences.